Study on optical properties of hexagonal lattice photonic crystal fibers infiltrated with heavy water - Dang Van, Trong; Le Tran, Bao Tran; Chu Van, Lanh (Communications in Physics, 2024)
In this paper, we analyzed a PCF made from fused silica glass, with a core filled with heavy water. The guiding properties of proposed fibers in terms of effective refractive index, attenuation, and dispersion of the fundamental mode were studied and optimized setups were selected and analyzed in detail. After 25 simulations, we determined two structures possessing optimal dispersion with the lattice constant (Ʌ) and the filling factor as follows: Ʌ = 1.1 µm, d/Ʌ = 0.92 for #F1 and Ʌ = 1.4 µm, d/Ʌ = 0.92 for #F2. Besides, high nonlinearity and low confinement loss are also outstanding points in our model. Thanks to these advantages, the proposed fibers have been targeted for flat and smooth broadband supercontinuum (SC) generation for near-infrared applications.